Reverberation Time and Power Model in Indoor Wireless Scenarios - She, Jun; Yu, Yu; Cui, Peng-Fei; Lu, Wen-Jun; Zhu, Hong-Bo (Společnost pro radioelektronické inženýrství, 2018)
A novel, room-electromagnetics-theory-based model for reverberation time, path gain and Power Delay Profile (PDP) is proposed. Unlike the traditional models describing only the reflections, the new model takes not only reflections at boundaries, but also the effects including scattering, diffraction and air absorption along the propagation path into consideration. Extensive measurements at 2.6 GHz under Line-Of-Sight (LOS) conditions are carried out not only in enclosed structures, but also in semi-enclosed scenarios which are normally with higher average absorptive coefficients. Hence, the application of reverberation model is extended compared to open literature. Reverberation time and path gain values predicted by the proposed model are in good agreement with these measurement results obtained in various indoor wireless environments. In addition, a novel PDP model with lower complexity is proposed based on measured path gain and Nakagami-m distribution. The proposed models are proved to be more accurate than traditional reverberation models.
Keywords: Indoor environment; reverberation time; path gain; Power Delay Profile (PDP); room electromagnetics